Implementasi Model Pembelajaran Problem Posing Di Sekolah Menengah Atas - kevin effriansyah; Camellia Camellia (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2006)
The development of technology in the modern era known as the 21st century, students' ability to formulate and test hypotheses is very important. The main objective of this study is to determine how the ability of students of SMA Negeri 16 Palembang to formulate and test their hypotheses is influenced by the problem posing learning model. This study uses a quantitative approach. The type of one group pre-test post-test is used for the pre-experimental design. One group pre-test post-test is a study that uses one class in the research process without any comparison group. Purposive sampling was used to select 36 students from class XI.4 from a population with the criteria of low ability to formulate and test hypotheses. Information was collected through tests. The findings showed a positive effect, the pre-test score for the first indicator increased from 33.33 to 69.79 in the post-test; for the second indicator, the pre-test score increased from 54.51 to 84.37 in the post-test. According to the analysis, the problem posing learning model helps students formulate hypotheses and test them well. Therefore, this model can be considered as an appropriate alternative approach for Pancasila education.